2018
DOI: 10.3892/mco.2018.1732
|View full text |Cite
|
Sign up to set email alerts
|

Levels of regulatory T cells and invariant natural killer cells and their associations with regulatory B�cells in patients with non-Hodgkin lymphoma

Abstract: Due to their immunoregulatory properties, several specialized cell subsets, including regulatory T (Treg), invariant natural killer T (iNKT) and regulatory B (Breg) cells, are involved in the pathogenesis of non-Hodgkin lymphoma (NHL). However, the interaction between various cells remains to be elucidated. The aim of the present study was to evaluate the levels of Treg, iNKT and Breg cell subsets and their interrelationships in the peripheral blood (PB) and bone marrow (BM) of patients with B-cell NHL who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This result is consistent with results from previous studies that have reported that an increased proportion of Tregs in PBMC is a poor prognostic factor in DLBCL patients [ 15 , 45 ]. However, low concentrations of Tregs in PBMC have also been observed in DLBCL patients, generating some controversy that still needs to be clarified [ 46 , 47 ]. In our study, we also evaluated the effect of treatment on Treg levels.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with results from previous studies that have reported that an increased proportion of Tregs in PBMC is a poor prognostic factor in DLBCL patients [ 15 , 45 ]. However, low concentrations of Tregs in PBMC have also been observed in DLBCL patients, generating some controversy that still needs to be clarified [ 46 , 47 ]. In our study, we also evaluated the effect of treatment on Treg levels.…”
Section: Discussionmentioning
confidence: 99%
“…In hematological convalescents, a reduced naïve and induced Treg population may lead to loss of suppressive function or an insufficient inflammatory response upon exposure to pathogens. This fact is particularly important in patients with lymphoid malignancies in whom function of CD4+, CD8+, and Treg cells is impaired due to the immunopathology of underlying disease and applied treatment 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…The level of Breg cells of patients with oesophageal carcinoma and gastric cancer was significantly higher than that in healthy controls [4,5]. Boulassel et al [20] found the levels of Breg cells were lower in patients with B cell non-Hodgkin lymphoma (NHL) compared with that of healthy controls, and the frequency of Breg cells was remarkably increased after R-CHOP chemotherapy. Previous research has shown that Breg cells promote human hepatocellular carcinoma (HCC) growth and invasiveness [6].…”
Section: Discussionmentioning
confidence: 99%